2021
DOI: 10.1186/s13071-021-04795-2
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA028466 regulates Th1/Th2 cytokine expression and associates with Echinococcus granulosus antigen P29 immunity

Abstract: Background Cystic echinococcosis (CE) is a parasitic disease that is caused by Echinococcus granulosus (Eg). The recombinant Echinococcus granulosus antigen P29 (rEg.P29) was shown to confer effective immunity to sheep and mice during E. granulosus secondary infection in our previous study. In this study, we sought to investigate the ability of long noncoding RNA 028466 (lncRNA028466) as a regulator for the protective immunity mediated by rEg.P29 vaccination and to study the effects of lncRNA02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Additionally, the lncRNA Dreg1 is intimately linked to the expression of GATA3 during Th2-cell differentiation and participates in the establishment of GATA3 expression ( Chan et al, 2021 ), suggesting that Dreg1 may promote Th2-cell differentiation. The expression of LncRNA028466 decreased after inoculation with recombinant Echinococcus granulosus antigen P29 vaccine, and studies have shown that LncRNA028466 can promote Th2-cell differentiation and the secretion of IL-10 and IL-4, but inhibits the secretion of Th1-related cytokines, IFN-γ and IL-2 ( Wang et al, 2021 ). Cystic echinococcosis is a chronic parasitic disease for which there is still no commercial vaccine due to the complex host-parasite relationship.…”
Section: Lncrnas Facilitate the Lineage Shift Between Th1 And Th2 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the lncRNA Dreg1 is intimately linked to the expression of GATA3 during Th2-cell differentiation and participates in the establishment of GATA3 expression ( Chan et al, 2021 ), suggesting that Dreg1 may promote Th2-cell differentiation. The expression of LncRNA028466 decreased after inoculation with recombinant Echinococcus granulosus antigen P29 vaccine, and studies have shown that LncRNA028466 can promote Th2-cell differentiation and the secretion of IL-10 and IL-4, but inhibits the secretion of Th1-related cytokines, IFN-γ and IL-2 ( Wang et al, 2021 ). Cystic echinococcosis is a chronic parasitic disease for which there is still no commercial vaccine due to the complex host-parasite relationship.…”
Section: Lncrnas Facilitate the Lineage Shift Between Th1 And Th2 Cellsmentioning
confidence: 99%
“…Cystic echinococcosis is a chronic parasitic disease for which there is still no commercial vaccine due to the complex host-parasite relationship. However, some effective antigens have been used as candidate vaccines for cystic echinococcosis prevention, such as recombinant Echinococcus granulosus antigen P29 ( Wang et al, 2021 ). LncRNA028466 may be involved in recombinant Echinococcus granulosus antigen P29 vaccination-mediated immune response by regulating the differentiation of CD4 + T cells during echinococcus granulosus infection ( Wang et al, 2021 ).…”
Section: Lncrnas Facilitate the Lineage Shift Between Th1 And Th2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMCs (5 × 10 5 ) were resuspended in 100 μL of Buffer2 (as prevous reported [ 32 ]) for the surface stain. Then, the surface markers were added to stain the cells for half-hour at 4 °C, protected from light.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the surface markers were added to stain the cells for half-hour at 4 °C, protected from light. For intracellular cytokine staining, samples were then fixed for 8 min protecting from light using 4% paraformaldehyde and permeabilised for 2 h in the dark using Buffer2 (as prevous reported [ 32 ]). After washing, the cells were stained using intranuclear antibodies in the dark for half-hour at 4 °C.…”
Section: Methodsmentioning
confidence: 99%